UNEQUAL ETHICAL WORLDS: THE EVERYDAY MANAGEMENT OF PIETY AMONG TABLIGHI WOMEN - Annisa Fitri Amaliah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2026)
This article examines how women in the Tablighi Jamaat in Bandung navigate piety across two different moral regimes: the intensive ethical spaces of the movement and the more plural moral terrain of everyday life. It focuses on how Tablighi women inhabit religious commitments through the niqab, bodily comportment, voice, and public interaction. Drawing on ethnographic research, including participant observation in masturah gatherings, informal conversations, and interviews with Tablighi women, the article shows that piety is not merely negotiated as a social strategy but lived as an embodied ethical navigation. Masturah represents an intensive ethical space in which women’s bodies are oriented toward discipline, adab, religious attachment, and affective solidarity. Everyday spaces, by contrast, require different bodily and social adjustments. The article argues that Tablighi women’s piety should not be understood as inconsistent, passive submission, or merely tactical negotiation. Rather, piety is a situated ethical practice through which women read, feel, and inhabit different moral demands without abandoning their religious orientation. By foregrounding movement across these moral regimes, the article proposes liminal agency as a way to understand how women sustain pious commitments across unequal moral worlds.